PEMBERLAKUAN KETENTUAN PASAL 21 UNDANG-UNDANG NOMOR 30 TAHUN 2014 DALAM PENANGANAN KORUPSI - Pudyatmoko, Yohanes Sri; Aryadi, Gregorius (Faculty of Law, Parahyangan Catholic University, 2021)
This research departs from the author’s observation that Indonesian government officials are currently very wary and worried being criminally charged for corruption and at the same time brought before the administrative court for abuse of power. The main question here is whether the possibility of being brought before the Administrative Court may or may not have positive effect. The main finding, using a legal normative approach, is that the final decision on the issue, whether there is abuse of power or not, as decided by the Administrative Court, would be important in proving disproving, the corruption charge brought before the criminal court.